Does the Provision of Public Goods Correspond to Local Demand? - Hongmei Yi; Denise Hare; Linxiu Zhang (Contemporary Economic Policy, 2011)
Recently China's central government has promoted public goods investment in pursuit of rural development and poverty reduction. However, the top down nature of investment planning may lead to mismatches between public goods projects and the demands of local residents. Using village- and household-level survey data, this study seeks to identify the determinants of project implementation, focusing on investments in roads, drinking water, and irrigation. Contrary to some popular perception, our results suggest symmetry between farmers' reported demand and the types of projects implemented in their villages. The relative contribution of local demand to project implementation is seen to vary, however, across different types of public goods. (JEL D71, H41, H77, P35)